Behavioral Interventions to Reduce Sexual Risk Behavior in Adults with HIV/AIDS Receiving HIV Care: A Systematic Review. - Laisaar, Kaja-Triin; Raag, Mait; Rosenthal, Marika; Uusküla, Anneli (AIDS patient care and STDs, 2015)
Regular interactions with people living with HIV/AIDS (PLWHA) who are receiving care provide caregivers opportunities to deliver interventions to reduce HIV-related risks. We conducted a systematic review of behavioral interventions for PLWHA (provided at individual level by caregivers at HIV care settings) to determine their efficacy in reducing sexual risk behavior. Conference websites and biomedical literature databases were searched for studies from 1981 to 2013. Randomized and quasi-randomized controlled trials (with standard-of-care control groups), considering at least one of a list of HIV-related behavioral or biological outcomes in PLWHA aged ≥18 receiving HIV care with at least 3-month follow-up were included. No language or publication status restrictions were set. Standardized search, data abstraction, and evaluation methods were used. Five randomized controlled trials were included in the review. We found limited evidence that sexual risk reduction interventions increase condom use consistency in HIV transmission risk acts, and reduce the number of (casual) sexual partners. We still believe that regular interactions between HIV care providers and PLWHA provide valuable opportunities for theory-based sexual risk reduction interventions to restrain the spread of HIV.
Keywords: Anti-HIV Agents; Behavior Therapy; Condoms; HIV Infections; Humans; Intervention Studies; Randomized Controlled Trials as Topic; Risk Reduction Behavior; Risk-Taking; Safe Sex; Sexual Behavior; Sexual Partners